2006
DOI: 10.1271/bbb.60365
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Exo-β-1,3-D-galactanase fromStreptomyces avermitilisNBRC14893 Acting on Arabinogalactan-Proteins

Abstract: A gene belonging to glycoside hydrolase family 43 (GH43) was isolated from Streptomyces avermitilis NBRC14893. The gene encodes a modular protein consisting of N-terminal GH43 module and a family 13 carbohydrate-binding module at the C-terminus. The gene corresponding to the GH43 module was expressed in Escherichia coli, and the gene product was characterized. The recombinant enzyme specifically hydrolyzed only -1,3-linkage of two D-galactosyl residues at non-reducing ends of the substrates. The analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…To date, all characterized exo-␤-1,3-galactanases have greater activity toward ␤-1,3-galactan than ␤-1,3/␤-1,6-galactan from Prototheca zopfii, LWAG, gum arabic, and radish roots (1,(3)(4)(5)(6)(7)21). BLLJ_1840 has low sequence identities (27% to 28%) with other exo-␤-1,3-galactanases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, all characterized exo-␤-1,3-galactanases have greater activity toward ␤-1,3-galactan than ␤-1,3/␤-1,6-galactan from Prototheca zopfii, LWAG, gum arabic, and radish roots (1,(3)(4)(5)(6)(7)21). BLLJ_1840 has low sequence identities (27% to 28%) with other exo-␤-1,3-galactanases.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, exo-␤-1,3-galactanase hydrolyzes the ␤-1,3-galactan backbone, bypassing ␤-1,6-galactan side chains, and consequently releases galactose, ␤-1,6-galactooligosaccharides, and their derivatives (1,2). Exo-␤-1,3-galactanases, which belong to glycoside hydrolase family 43 (GH43), have been cloned and characterized from several sources, including bacteria and fungi (1,(3)(4)(5)(6)(7).…”
mentioning
confidence: 99%
“…We cloned two kinds of galactanases: exo-␤-1,3-galactanase (EC 3.2.1.145) from Phanerochaete chrysosporium and endo-␤-1,6-galactanase (EC 3.2.1.164) from Trichoderma viride, and demonstrated that the enzymes were novel and could be classified as glycoside hydrolase family 43 (GH43) and family 5 (GH5), respectively (7-9) (see the CAZy website). Genes encoding proteins similar to such enzymes were also identified in the Streptomyces avermitilis genome (10,11).…”
mentioning
confidence: 99%
“…These enzymes hydrolyze -1,3-galactan and -1,6-galactan, respectively, which constitute the backbone of the type II arabinogalactan present in AGP sugar linkages. [69][70][71] When the bacterium was cultivated with gum arabic (a kind of AGP) as carbon source, L-arabinose was released from the AGPs, and this led to the isolation of a novel -L-arabinopyranosidase, SaArap27. The sequence of the SaArap27-encoding gene indicated that the protein possessed 614 amino acid residues (after removal of a putative N-terminal signal peptide) and a molecular weight of 64 kDa.…”
Section: Cbm13 Of Streptomyces Avermitilis -L-arabinopyranosidasementioning
confidence: 99%